IMPLIKASI PENITIPAN ANAK YANG BERKONFLIK DENGAN HUKUM DI BALAI PERLINDUNGAN DAN REHABILITASI SOSIAL REMAJA TERHADAP PUTUSAN HAKIM - Genjah Pulung Jati; Fransisca Romana Harjiyatni (Universitas Janabadra, 2022)
This thesis is the result of research on children who commit criminal acts, also known as children in conflict with the law, who are placed in the Youth Social Protection and Rehabilitation Center to serve their criminal period during the legal process. The legal process that must be followed takes a long time, ranging from four months to one year. The length of the legal process does not guarantee that the criminal sentence served by the child at the Youth Social Protection and Rehabilitation Center after the judge's verdict will be reduced or not. The context of this study is children who have run afoul of the law and have been placed in the Youth Social and Rehabilitation Center after receiving a judge's judgment; some have received a cut, while others have not, during their criminal sentence at the Social Protection and Rehabilitation Center. Adolescents and the factors that judges evaluate when making decisions about who gets a reduction and who doesn't in their criminal period at the Youth Social Protection and Rehabilitation Center. The goal of this research is to determine and assess the consequences of placing children in legal trouble at the Youth Social Protection and Rehabilitation Center in opposition to a judge's decision.The results of the study revealed that the implication of placing children in conflict with the law at the Youth Social Protection and Rehabilitation Center against the judge's decision is that in the judge's decision, there are children who receive a reduction and those who do not receive a reduction in the criminal period that has been served by the child judge at the Youth Social Protection and Rehabilitation Center, The judge considers the law, indictments/legal facts, results of the Litmas Penitentiary (BAPAS), prosecutors' demands, pleas, and public figures' opinions when deciding related cases, namely reducing or not reducing the criminal period that has been served by children at the Youth Social Protection and Rehabilitation Center said. When it comes to deciding whether to reduce or not reduce the criminal time, children who are placed in the Juvenile Social Protection and Rehabilitation Center must have a clear status; if they are prisoners, they must be deducted formally under the Criminal Procedure Code. If the child is neither a prisoner or a law enforcement officer, the judge considers whether the child's care or placement restricts his or her freedom. The judge may consider lowering the time of care/placement if it restricts the child's independence. In terms of lowering the child's criminal period while at the Balai, this can be factored into the decision, specifically in the legal reasons for imposing sanctions and in mitigating circumstances.